A predictive data-driven model for traffic-jams forecasting in smart santader city-scale testbed - Treboux, Jerome; Jara, Antonio J.; Dufour, Luc; Genoud, Dominique (2015 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2015)
In this paper, a model for traffic jam prediction using data about traffic, weather and noise is presented. It is based on data coming from a Smart City in Spain called Santander. The project in this city is called "Smart Santander" and provides a platform for large-scale experiment based on realtime data. This paper demonstrates the possibility of predicting traffic jams and is a basis to integrate in projects to improve the quality of services. In this work, a cross validation method to ratify our training set is proposed. Data intelligence analysis techniques are used for the prediction with an implementation of Neural Network and Decision Tree algorithms. These algorithms are using different parameters coming from Smart Santander and other external sources. Furthermore, a cross validation process is also integrated to improve the final result. The traffic jam prediction for the next 15 minutes reached an accuracy of 99.95%.